(untitled) (Research, Society and Development, 2025)
Child development is a continuous and interdependent process involving physical, cognitive, emotional, and social transformations, influenced by biological, psychological, and environmental factors. This study aims to analyze the importance of physical and sporting activities in the integral development of the child, considering cognitive, motor, social, and emotional aspects, as well as the role of the school, family, and public policies in this process. This is a bibliographic and qualitative research study, based on authors such as Piaget, Gallahue, and Ozmun, who address cognitive, motor, and psychomotor development, as well as guidelines from the Statute of Children and Adolescents (ECA) and recent studies on human development, sports, and education. The results indicate that the practice of physical and sporting activities significantly contributes to the improvement of motor, cognitive, and socio-emotional skills, promoting socialization and self-concept. Furthermore, the school, in particular, stands out as an essential mediator between knowledge and bodily experience, promoting not only physical development but also values and social bonds. It is concluded that encouraging physical activity from childhood is essential for the healthy and integral development of the individual and should be understood as part of an educational and social process that involves family, school and community.